(untitled) (Research, Society and Development, 2020)
The aim of the present work was to evaluate the production of blackberry seedlings (Morus nigra) propagated by stalks on substrates with different levels of rice straw (Oryza sativa). The experiment was carried out in a green house (with 50% luminosity) at the Center of Agrarian and Environmental Sciences (CCAA), Federal University of Maranhão (UFMA). The design was entirely randomized, with six treatments referring to the growing percentages of rice straw in natura (0, 20, 40, 60, 80, 100 %) combined with soil, with four repetitions and 16 plants per plot. At 30 days after sowing the following were measured: percentage of survival of cuttings, leaf area; height of the largest sprout; diameter of the largest sprout; root length; root volume; dry mass of the aerial and root part; and the Dickson quality index was also determined. With excision of the survival percentage variable, which did not even meet the assumptions of normality and homoscedasticity of variance analysis (ANOVA), in all other variables a significant effect (p<0.01) of the treatments formulated on the growth of blackberry seedlings was observed. In general, the substrates containing rice husks in natura provided increases in the values of almost all characteristics assessed. It can be concluded that the production of blackberry seedlings (Morus nigra) can be enhanced by adding up to 40% of fresh rice husk to the substrate composition.